Enhancing machine vision accuracy through programmable infrared sensors using van der Waals heterostructures - Chen, Xiaoyang (Nanyang Technological University, 2025)
This article explores the potential of programmable infrared (IR) sensors utilizing van der Waals heterostructures to improve accuracy and versatility of machine vision systems. The van der Waals heterostructure is composed of stacked 2D materials such as graphene, transition metal disulfide, and black phosphorus, which have adjustable optical-electronic properties and solve the limitations of traditional infrared sensors, such as high-power consumption, fixed sensitivity, and environmental constraints. By dynamically adjusting the sensitivity and spectral response, these programmable sensors show excellent adaptability, enabling them to be integrated into a variety of applications, including autonomous vehicle, industrial automation and environmental monitoring.